The Effect of Professional Competencies on Job Performance: A Literature Review - Jie, Cao; Naha Abu Mansor, Nur; Widarman Yus Kelana, Beni (International Journal of Psychosocial Rehabilitation, 2020)
Professional competencies play an essential role in improving employee’s job performance. However, previous studies neglect the effect of competency components, namely knowledge, skills, traits, motives and self-concept on job performance. Therefore, this paper aims to give an overview of the effect of professional competencies and its constructs on job performance through reviewing previous literatures. A conceptual model is proposed on the basis of literature review. And the finding reveals that whether professional competencies and its construct can affect job performance in different situations is still need to be confirmed.